From scrolls to traditions: a festschrift honoring Lawrence H. Schiffman - Miller, Stuart S.; Swartz, Michael D.; Fine, Steven; Grunhaus, Naomi; Jassen, Alex P.; Schiffman, Lawrence H. (The Brill reference library of ancient Judaism, 2020)
Contents -- Preface -- A Word about Abbreviations of Journal Titles and Textual Sources -- The Publications of Lawrence H. Schiffman / Compiled by Patrick J. Angiolillo and Joshua Blachorsky with the assistance of Marlene Schiffman -- Part 1 Biblical and Second Temple Period -- Probing the Jewish Setting of Matthew 11:25-30 / Joseph L. Angel -- Demons and Dominion: Forcing Demons into the Divine Order in Jubilees and the Dead Sea Scrolls / Miryam T. Brand -- Resistance and Appropriation: The Zoroastrian Context of the Book of Tobit / David Brodsky -- The Scholasticization of Religion: From Qumran to Ctesiphon / Yaakov Elman, z'l, in collaboration with Mahnaz Moazami -- The Power of Pain: A Literary Reading of the Wicked Priest's Death(s) in 1QpHab 99 / Alexandria Frisch -- Concerning tsedaqah: Reexamining the Gospels' Teaching on Charity within the Larger World of Ancient Jewish Halakah / Jeffrey Paul García -- The Unfinished Scroll Reconsidered: 11Q19 Column 67 / Andrew D. Gross -- The Early Study of Jewish Law in the Damascus Document: Solomon Schechter and Louis Ginzberg in Conversation and Conflict / Alex P. Jassen -- The Legacy of the Flood in the Book of Jubilees / Ari Mermelstein -- Part 2 Rabbis, Other Jews, and Neighboring Cultures -- An Aramaic Power of Attorney from Ramla (1056) [T-S 13 J 114]: A Translation and Genizah Study / Ross Brann -- The Treason of Yosa Meshita (Genesis Rabba 65:27): A Rabbinic Reflection on the Fate of the Temple Lampstand / Steven Fine -- Radak's Engagement with Rabbinic Literature in His Sefer ha-Shorashim: Innovations in Light of His Predecessors' Approaches / Naomi Grunhaus -- A Tale of Two or Three Witnesses: Witness Testimony in Greco-Roman, Qumranic, and Rabbinic Court Procedure / Richard Hidary -- A Creation Sui Generis: The Evolution of a Concept / Sarra Lev -- All Law begins with Custom: Rabbinic Awareness of Popular Practice and its Implications for the Study of the Jews of Roman Palestine / Stuart S. Miller -- The Eiruv and the Outsider: A Study in Urban Conditions in Roman Palestine / Adam Mintz -- Telling Retellings: Honi the Circlemaker and the Development of Tannaitic Aggadic Discourse / Aaron D. Panken, z'l -- A New Edition of Az nefesh kol ḥai, Yannai's Qedushta for Leviticus 4:1-35 / Michael Rand -- Jacob's Image: The History of a Late Antique Motif / Alexei M. Sivertsev -- Civil and Uncivil Magic: Individual, Community, and Identity in Ancient and Medieval Jewish Curse Texts / Michael D. Swartz -- General Index.